Whole-gene CFTR sequencing combined with digital RT-PCR improves genetic diagnosis of cystic fibrosis - Straniero, Letizia; Soldà, Giulia; Costantino, Lucy; Seia, Manuela; Melotti, Paola; Colombo, Carla; Asselta, Rosanna; Duga, Stefano (Journal of human genetics, 2016)
Despite extensive screening, 1-5% of cystic fibrosis (CF) patients lack a definite molecular diagnosis. Next-generation sequencing (NGS) is making affordable genetic testing based on the identification of variants in extended genomic regions. In this frame, we analyzed 23 CF patients and one carrier by whole-gene CFTR resequencing: 4 were previously characterized and served as controls; 17 were cases lacking a complete diagnosis after a full conventional CFTR screening; 3 were consecutive subjects referring to our centers, not previously submitted to any screening. We also included in the custom NGS design the coding portions of the SCNN1A, SCNN1B and SCNN1G genes, encoding the subunits of the sodium channel ENaC, which were found to be mutated in CF-like patients. Besides 2 novel SCNN1B missense mutations, we identified 22 previously-known CFTR mutations, including 2 large deletions (whose breakpoints were precisely mapped), and novel deep-intronic variants, whose role on splicing was excluded by ex-vivo analyses. Finally, for 2 patients, compound heterozygotes for a CFTR mutation and the intron-9c.1210-34TG T allele-known to be associated with decreased CFTR mRNA levels-the molecular diagnosis was implemented by measuring the residual level of wild-type transcript by digital reverse transcription polymerase chain reaction performed on RNA extracted from nasal brushing.